2021
DOI: 10.1021/acs.langmuir.1c01639
|View full text |Cite
|
Sign up to set email alerts
|

Impact Dynamics and Freezing Behavior of Surfactant-Laden Droplets on Non-Wettable Coatings at Subzero Temperatures

Abstract: The present study investigates the impact and freezing behavior of the droplets of surfactant solutions on non-wettable coatings at very low temperatures of −10 to −30 °C. Our goal is to elucidate the critical role of concentration, molecular weight, and ionic nature of surfactants on these phenomena. To achieve this goal, we used sodium dodecyl sulfate (anionic), hexadecyltrimethylammonium bromide (cationic), and n-decanoyl-n-methylglucamine (nonionic) at four concentrations ranging from 0 to 2 × CMC (critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The droplet impact can cause deposition, rebound and splashing, and then affects the ice accumulation and growth on solid surfaces [10]. Hence, in order to better understand the antiicing mechanisms of superhydrophobic surfaces and propose new anti-icing technologies, the dynamics and heat transfer processes of droplet impingement and freezing process should be considered and investigate [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The droplet impact can cause deposition, rebound and splashing, and then affects the ice accumulation and growth on solid surfaces [10]. Hence, in order to better understand the antiicing mechanisms of superhydrophobic surfaces and propose new anti-icing technologies, the dynamics and heat transfer processes of droplet impingement and freezing process should be considered and investigate [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that droplets can rebound from the superhydrophobic surface to inhibit icing when the time scale of the nucleus/ regalience is greater than the contact time [29,30]. On the another hand, the anti-icing performance for example icing delay time, freezing temperature and dynamical process of icing have been investigated deeply [11][12][13]31]. But, limited literature is available about the volume changes and freezing front speed during freezing of water droplets on superhydrophobic surfaces with different undercooling.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Samah et al 36 reported the adhesion of impacting droplets on the SHS of 4 °C due to the appearance of condensed microdroplets on that surface. Esmaeili et al 37 added surfactants to pure water and observed faster freezing than in pure water because the Cassie−Baxter to Wenzel transition results in a higher thermal conductivity and a larger interfacial area. In addition, Chu et al 38 claimed that the Cassie frost generated on the SHSs at low temperatures can be removed easily by an impacting droplet, and thus, the droplet might still rebound from the surface under condensed conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Droplet impact events on SHSs of low temperatures are different from those that occur at room temperature, on account of the heat exchange and the ice nucleation at the solid–liquid interface. Previous research has clarified the rebound or adhesion dynamics of impacting droplets with several mechanisms, including but not limited to nucleation and icing, viscosity change, wettability transition, and surface frosting. , For instance, Ding et al characterized the droplet rebound energy and the mass fraction of the secondary droplets and proposed that ice nucleation reduces the droplet rebound capacity when the residual kinetic energy is less than 35%. Zhang et al found that the high-speed impingement of droplets on textured SHSs dramatically increases the solid–liquid contact area, causing higher nucleation rates and lower critical adhesion temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The impact behavior of the drops on the solid substrate is a frequently studied phenomenon in fluid mechanics because of numerous industrial and daily applications ranging from spray coating, inkjet printing, , aeronautics, , to criminal forensics . During the impact process, there are two main stages, including spreading and retraction, and various outcomes of the drop, such as splash, deposition, and rebound, , which are highly determined by liquid properties (e.g., size, density, viscosity, surface tension), substrate properties (e.g., wettability, roughness, surface nano/microstructure, shape, elasticity, or porosity), and impact conditions (e.g., impact velocity, environment temperature and humidity, gas pressure, and so on). , Among these, the design of surface structures is the most commonly used method to tune the droplet dynamics . Generally speaking, the control of the drop impact dynamics for application has two aspects.…”
Section: Introductionmentioning
confidence: 99%